How Situation Affects Risk Taking Behavior - Dananjaya, Dr. Yanuar (International Journal of Scientific Research and Management (IJSRM), 2020)
This paper examines how situation affects risk taking behavior. Two theories predict different outcomes on the effect of situation to risk taking. House Money Effect predicts that positive situation will result in increased risk taking due to availability of slack that can be risked. On the other hand, negative situation will decrease risk taking because of reduced slack. Thus House Money Effect describes positive relation between situation and risk taking behavior. On the contrary according to Reflection Effect from Prospect Theory, human beings are risk averse in gain situation but risk seeking in loss situation. Reflection Effect thus predicts that positive situation will result in decreased risk taking while negative situation will result in increased risk taking, in other word negative relation between situation and risk taking. To test which theory better describes the relation between situation and risk taking behavior, we examine how company performance affects risk taking behavior of the top management. Company performance is proxied using Return of Asset. Risk taking behavior is proxied using change of debt level. The result shows negative relation between situation and risk taking, and thus support Reflection Effect in Prospect Theory.